Dealing with them preparing state and local officials for the cross-cultural challenge. - Chadwin, Mark Lincoln; Kim, Pan Suk; Rogers, Sandra E. (1995)
"What can state and local officials do to prepare themselves for their role in the global economy? With state and local governments expanding their efforts to promote exports and attract foreign investment, encounters with officials from foreign corporations and government have increased. The issue of how to prepare for these cross-cultural encounters is rarely addressed. This article provides some tools for thinking systematically about techniques for cross-cultural training and making cost-efficient decisions about appropriate actions in different situations"
Keywords: Public officials; Local government; Civil service